Kavain Alleviates Choroidal Neovascularization Via Decreasing the Activity of the HIF-1α/VEGF-A/VEGFR2 Signaling Pathway and Inhibiting Inflammation - Xi Chen; Xun Qin; Wen Bai; Junsong Ren; Yang Yu; Huiling Nie; Xiumiao Li; Zhangyu Liu; Jiayu Huang; Juxue Li; Jin Yao; Qin Jiang (Advanced Pharmaceutical Bulletin)
Purpose: Neovascular age-related macular degeneration (nAMD) is a prevalent cause of blindness in the elderly. Standard treatment includes anti-vascular endothelial growth factor (anti-VEGF) drugs, such as aflibercept. However, anti-VEGF drugs may have limited efficacy and cause drug resistance. This study explores whether Kavain, an anti-inflammatory molecule from Piper methysticum, can treat choroidal neovascularization (CNV). Methods: Various experiments were conducted to assess the Kavain’s toxicity. The impact of Kavain on in vitro cultured endothelial cells was examined through 5-ethynyl-20-deoxyuridine (EdU) assays, transwell migration assays, and tube formation assays. The therapeutic effects of Kavain on CNV were investigated using a laser-induced CNV mice model. To elucidate the mechanism of Kavain, network pharmacology analysis, molecular docking, and western blots were performed. Results: Kavain exhibited no apparent toxicity both in vitro and in vivo. Kavain significantly decreased endothelial cell viability, proliferation, migration, and tube formation ability in a dose-dependent manner compared to the hypoxia groups (P<0.05). Kavain alleviated CNV in the laser-induced CNV mouse model compared to the control groups (P<0.05). These effects were statistically significantly enhanced in the Kavain plus aflibercept groups (P<0.05). Following Kavain administration, the expression levels of various inflammatory factors were markedly reduced in retinal pigment epithelium (RPE)/choroid complexes (P<0.05). Mechanistically, Kavain decreased the activity of the hypoxia-inducible factor 1α (HIF-1α)/VEGF-A/ VEGF receptor 2 (VEGFR2) signaling pathway. Conclusion: Our study is the first to demonstrate Kavain’s potential as a promising treatment for nAMD, owing to its dual effects of anti-inflammation and anti-angiogenesis.